Social capital in action: the role of civic engagement in individuals' savings behavior in the United Kingdom - Agrawal, Adya (Nanyang Technological University, 2024)
The concept of social capital encompassing social ties, civic behaviors, and trust has been researched in the literature, in connection with various economic and financial outcomes (Sadlowska & Rees, 2022; Scrivens & Smith, 2013). The current study investigated the relationship between civic engagement, a dimension of social capital, and individual savings, focusing on the United Kingdom. The United Kingdom Household Longitudinal Study (UKHLS) dataset was used for the research and social capital was proxied using volunteering dummy and volunteering frequency variables. The findings based on comprehensive regression analysis suggested a positive association between the two variables as volunteers were found to have higher savings than non-volunteers. However, analysis using the volunteering frequency variables showed that this relationship became negative at high volunteering levels. Lagged effects from this frequency measure as well as a gender influence on the volunteering-savings relationship were also found. The findings of this study contribute to the broader literature on social capital and the understanding of how it can be utilized for generating better individual and national financial and economic outcomes. Continued research on this topic in the context of other countries and with varying methodologies is important to comprehensively understand the importance of social capital.